Calderbank Offer sebagai Instrumen untuk Meningkatkan Efisiensi di BANI Arbitration Center - Adhim, Lalu; Dewi, Sinta; Maulana, Mursal (UI Scholars Hub, 2025)
This article explores the shifting landscape of international arbitration, traditionally valued for its efficiency. Today, increased costs and prolonged dispute resolution processes change this perception. The article introduces the Calderbank offer, a strategic instrument from common law that promotes early settlement. By integrating civil law’s adversarial approach and practice to settle with settlement offer in common law, this concept aligns with peace theory and could enhance efficiency in BANI Arbitration Center. This instrument allows arbitral tribunals to impose cost penalties on parties who reject settlement offers and subsequently fail to achieve a more favorable award. In this research, the authors employ a normative juridical research method, utilizing literature review as the primary approach. This research indicates that adopting the Calderbank offer may encourage parties to objectively consider the settlement offer, potentially leading to a win-win solution. BANI Arbitration Center may adopt this instrument, as BANI Rules has included provisions on tribunal discretion in cost allocation.